Interacting and communicating with children: an exploratory study about educators' behavior during a collaborative activity. Issue 6 (2nd November 2022) - Fuertes, Marina; Almada, Maria João; Braz, Matilde; Lopes, Joana
ABSTRACT: Educators' acts and verbalizations toward children during daily routines can promote children's early participation, self-agency, and self-esteem. In this study, we investigate the association between the educator's type of Verbalizations (Number of Suggestions, Directions, Orders, Positive and Negative Feedback, Teaching, Questions) and the quality of their Interactive Behavior (cf. Empathy, Pedagogical Challenging, Cooperation, Reciprocity and Engagement behavior) during a collaborative activity with a child. Sixty-four educator-child dyads, with children ranging from 3- to 5-years old and educators with more than five years of professional experience, were observed while manufacturing a product of their choice for 20 min using predefined materials and tools. Videos were scored according to the Tandem guidelines and scales. Our findings suggest that the educator's verbalizations and interactive behavior are associated, creating a relational context that shapes interactions and children's participation.